Update on the Mechanism and Treatment of Sevoflurane-Induced Postoperative Cognitive Dysfunction - Wang, Cong-mei; Chen, Wei-can; Zhang, Yan; Lin, Shu; He, He-fan (Frontiers in Aging Neuroscience, 2021)
Sevoflurane is one of the most widely used anesthetics for the induction and maintenance of general anesthesia in surgical patients. Sevoflurane treatment may increase the incidence of postoperative cognitive dysfunction (POCD), and patients with POCD exhibit lower cognitive abilities than before the operation. POCD affects the lives of patients and places an additional burden on patients and their families. Understanding the mechanism of sevoflurane-induced POCD may improve prevention and treatment of POCD. In this paper, we review the diagnosis of POCD, introduce animal models of POCD in clinical research, analyze the possible mechanisms of sevoflurane-induced POCD, and summarize advances in treatment for this condition.